Cardiovascular changes in patients with SARS-CoV-2 submitted to intensive care: Scope review (Research, Society and Development, 2021)
Objective: to map the scientific literature on cardiovascular alterations with the highest incidence in patients with SARS-CoV-2 submitted to intensive care units. Method: scoping review following the design of the Joanna Briggs Institute. Contemplated the bases of white and gray literature, without temporal and idiomatic restriction. Three stages of study selection were performed: selection by title and abstract; reading in full the selected studies and reading the references of the included studies. The included studies were presented in narrative synthesis and tables. Results: a total of 2269 publications were obtained, obtaining eight studies after the selection steps. The most relevant findings were: leukocytopenia, increase in cardiac necrosis markers, alteration of the ST segments, thickening of the left ventricle and reduction in left ventricular ejection flow. Conclusion: the cardiac alterations with the highest incidence found in these patients were those caused by the inflammatory response in the heart and the overload of the cardiac pump.